2020
DOI: 10.1002/pat.5030
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and chemical modification of crystalline nanocellulose to reinforce natural rubber composites

Abstract: Potential of crystalline nanocellulose (CNC), as green reinforcing filler, has been evaluated for the preparation of natural rubber (NR) composites. CNC is derived from a natural source (ramie fiber) and its surface is modified with different organosilanes to strengthen the rubber‐filler interaction at the interface. It is found that, although at 2.5 phr (parts per hundred parts of rubber) loading of CNC the mechanical property of the NR composites is improved, it deteriorates at 5 phr loading. Surface modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…In addition, non-polar natural rubber also restricted the well-dispersion of polar CNC in the natural rubber matrix. This problem was overcome by the surface modification of CNC with (3-Aminopropyl)triethoxysilane (APTES), where the polar nature of the CNC was reduced after modification [ 54 ]. Moreover, aliphatic chains from APTES could coat over the surface of CNC and improve its compatibility with natural rubber.…”
Section: Surface Modification Of Nanocellulose For Natural Rubber Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, non-polar natural rubber also restricted the well-dispersion of polar CNC in the natural rubber matrix. This problem was overcome by the surface modification of CNC with (3-Aminopropyl)triethoxysilane (APTES), where the polar nature of the CNC was reduced after modification [ 54 ]. Moreover, aliphatic chains from APTES could coat over the surface of CNC and improve its compatibility with natural rubber.…”
Section: Surface Modification Of Nanocellulose For Natural Rubber Nanocompositesmentioning
confidence: 99%
“…The crystallinity of the nanocellulose was reduced by chemical modification and subsequently weakened its reinforcement potential in polymer composites [64]. However, Singh et al [54] proved that the silylation treatment did not affect the crystallinity of the CNC adversely as the modification only occurred mostly at the surface of the CNC. In a study by Somseemee et al [55], the crystallinity of the CNF modified by Bis-(triethoxysilylpropyl) tetrasulfide (TESPT) showed a slight decrease from 74.3% to 69.5%.…”
Section: Silylationmentioning
confidence: 99%
“…10 However, the researchers found that nanocellulose was a widely sourced, renewable and biodegradable green material with high strength, high modulus, crystallinity, and other characteristics, which has the potential to be an green filler for reinforcing polymer composites. [11][12][13][14] In recent years, the number of publications and literatures on nanocellulose has increased year by year. [15][16][17][18] Among them, there were many studies on nanocellulose reinforced rubber composites.…”
Section: Introductionmentioning
confidence: 99%
“…Integral blending method is widely used in the rubber‐filler system because of its simplicity and possible cost advantages 26–29 . In this method, TESPT is used as a simple additive during the compounding of rubber on two‐roll mixing mill or internal mixer.…”
Section: Introductionmentioning
confidence: 99%